Ketrampilan Bernalar Kritis Siswa SMK dengan Model Problem Based Learning: Tinjauan Literatur Sistematis - Heron; I Nyoman Tika; Ida Bagus Putu Arnyana; I Wayan Redhana (Jurnal Penelitian Pendidikan IPA, 2025)
A learning approach that has been extensively researched and proven effective in improving critical thinking skills is problem-based learning, or PBL. This learning model focuses on real-world problems. It encourages students to actively engage in the process of identifying, assessing, and developing collaborative solutions. Critical reasoning skills are essential for students to support independent thinking and problem-solving. The purpose of this study was to determine the critical reasoning skills of vocational high school students using the Problem Based Learning (PBL) model. The method used was a Systematic Literature Review (SLR). The articles used were sourced from Google Scholar and Crossref with the help of the Publish or Perish (PoP) application with a period of 2020-2025. All articles were sorted according to established criteria and had themes relevant to critical reasoning and problem-based learning, then collected a total of 17 articles. The results showed that the application of critical reasoning encouraged students to analyze, evaluate, and draw conclusions based on evidence, while PBL provided a real context for solving problems, developing problem-solving skills, and collaboration. Factors such as learning models, learning motivation, and learning environment influenced the critical reasoning of vocational high school students. These findings provide a deeper understanding of the application of the problem-based learning (PBL) model in improving critical reasoning of vocational high school students.